Simplified reliability analysis of punching in reinforced concrete flat slab buildings under accidental actions. (1st January 2017) - Olmati, P.; Sagaseta, J.; Cormie, D.; Jones, A.E.K.
Highlights: Proposed punching shear time history analysis for accidental actions. Case study of column removal in a flat slab concrete building. Dynamic amplification factor for load and rotation in slab-column connections. Proposed simplified reliability analysis for punching for accidental actions. Further studies for alternative damage scenarios: falling slab and blast load. Abstract: Flat slab concrete buildings are widely found in infrastructure such as office and residential buildings or industrial facilities. The susceptibility of progressive collapse of such structures due to accidental loads is highly dependent on the structural performance of the slab-column connections. This paper presents a framework for a simplified reliability analysis and derivation of safety factors for computing the probability of punching of flat slab concrete buildings subjected to accidental loads such as column removal, slab falling from above or blast load. The main advantage of the proposed approach is that it considers in a simple manner, the uncertainty in the gravity load applied in the slab before the accidental event, which affects the inertial effects and demand/capacity ratio in the slab-column connections. Eurocode 2 and the Critical Shear Crack Theory for punching are used and extended to dynamic cases for the assessment of the demand/capacity ratio using computer-based time history finite element simulations. The proposed reliability method is applied to a case study of an existing building showing that the column removal situation is not always critical whereas the slab falling from above is much more detrimental.